2020
DOI: 10.3390/su12219263
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Spatial Configuration and the Fourth Sustainable Dimension Creativity in University Campuses: The Case Study of Zernike Campus, Groningen, The Netherlands

Abstract: To date, little is known about the spatial aspects of the creativity of university campuses and their public spaces. This study recognises that creativity is the fourth sustainability, because the spatial configuration of campuses and city-university accessibilities are ‘creative solutions’ conceived for human needs. At the same time, creative ideas depend on interactions between individuals and the built environment. Therefore, based on the theoretical framework of the scholars who have explored the spatial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…In line with that, multiple studies have explored the effect of the built environment on the uses, perceptions, and behavior of people in public spaces through an empirical or theoretical perspective (Kytta et al, 2012; Ewing and Clemente, 2013; Mehta, 2014; Hadavi et al, 2015; Ghavampour et al, 2017) and specifically in campuses’ public spaces (Kenney et al, 2005; Strange and Banning, 2015; Hajrasouliha, 2017; Soares et al, 2020a,b, 2021). These studies established ideas on how public spaces could be physically improved through strategic guidelines, such as campus design, urban design, or public spaces guidelines.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with that, multiple studies have explored the effect of the built environment on the uses, perceptions, and behavior of people in public spaces through an empirical or theoretical perspective (Kytta et al, 2012; Ewing and Clemente, 2013; Mehta, 2014; Hadavi et al, 2015; Ghavampour et al, 2017) and specifically in campuses’ public spaces (Kenney et al, 2005; Strange and Banning, 2015; Hajrasouliha, 2017; Soares et al, 2020a,b, 2021). These studies established ideas on how public spaces could be physically improved through strategic guidelines, such as campus design, urban design, or public spaces guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, effective evidence improves EBP (Keen, 1980; Hamilton et al, 2019), increases the ability of an individual or a group to make decisions, and strengthens the research-practice interface through research-led decision-making in practice (Tennøy et al, 2016). In this research, the “research-generated evidence” was generated by multiple sources of theory and data-driven knowledge (analog and digital) on socio-spatial aspects of creativity––operationalized and measured as the causal relationships between the physical environment and creativity (the evidence was extracted from Soares et al, 2020a,b, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between spatial configurational attributes and social interactions remains in question. In the context of the urban environment, some exploratory studies have revealed the significant impact of space configurational features on social interactions within urban spaces [29][30][31]. Soares et al investigated the potential associations between spatial configuration and the possibility of socialization on school campuses [30].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the urban environment, some exploratory studies have revealed the significant impact of space configurational features on social interactions within urban spaces [29][30][31]. Soares et al investigated the potential associations between spatial configuration and the possibility of socialization on school campuses [30]. Focusing on in-between spaces, Can and Health revealed that street connectivity is important for long-duration activities and social interactions [29].…”
Section: Introductionmentioning
confidence: 99%